Central sensorimotor integration assessment reveals deficits in standing balance control in people with chronic mild traumatic brain injury - Campbell, Kody R.; King, Laurie A.; Parrington, Lucy; Fino, Peter C.; Antonellis, Prokopios; Peterka, Robert J. (Frontiers in Neurology, 2022)
Imbalance is common following mild Traumatic Brain Injury (mTBI) and can persist months after the initial injury. To determine if mTBI subjects with chronic imbalance differed from healthy age- and sex-matched controls (HCs) we used both the Central SensoriMotor Integration (CSMI) test, which evaluates sensory integration, time delay, and motor activation properties and the standard Sensory Organization Test (SOT). Four CSMI conditions evoked center-of-mass sway in response to: surface tilts with eyes closed (SS/EC), surface tilts with eyes open viewing a fixed visual surround (SS/EO), visual surround tilts with eyes open standing on a fixed surface (VS/EO), and combined surface and visual tilts with eyes open (SS+VS/EO). The mTBI participants relied significantly more on visual cues during the VS/EO condition compared to HCs but had similar reliance on combinations of vestibular, visual, and proprioceptive cues for balance during SS/EC, SS/EO, and SS+VS/EO conditions. The mTBI participants had significantly longer time delays across all conditions and significantly decreased motor activation relative to HCs across conditions that included surface-tilt stimuli with a sizeable subgroup having a prominent increase in time delay coupled with reduced motor activation while demonstrating no vestibular deficits. Decreased motor activation compensates for increased time delay to maintain stability of the balance system but has the adverse consequence that sensitivity to both internal (e.g., sensory noise) and external disturbances is increased. Consistent with this increased sensitivity, SOT results for mTBI subjects showed increased sway across all SOT conditions relative to HCs with about 45% of mTBI subjects classified as having an ‘aphysiologic’ pattern based on published criteria. Thus, CSMI results provided a plausible physiological explanation for the aphysiologic SOT pattern. Overall results suggest that rehabilitation that focuses solely on sensory systems may be incomplete and may benefit from therapy aimed at enhancing rapid and vigorous responses to balance perturbations.